Comparison of Diabetes Risk Following Smoking Cessation Treatment Using Varenicline Versus Bupropion Among Obese Smokers. (10th November 2015) - Yang, Mo; Chen, Hua; Johnson, Michael L.; Essien, Ekere James; Peters, Ronald J.; Wu, I-Hsuan; Abughosh, Susan M.
Abstract : Background: Recent literature suggests an initial increased risk of diabetes following smoking cessation. Objectives: To compare the risk of developing diabetes among obese smokers who tried to quit smoking using bupropion versus varenicline. Methods: A population-based retrospective cohort study was conducted using the General Electric (GE) electronic medical record database (2006–2011). The cohort consisted of obese adult smokers without a diabetes diagnosis at baseline and newly initiating use of either bupropion or varenicline. This cohort was then followed for 1 year to observe the risk of developing diabetes. The relative risk of bupropion versus varenicline on developing diabetes was assessed using Cox Proportional Hazards regression model after controlling for covariates. Results: The sample comprised of 78, 002 obese smokers of which 1, 937 (2.36%) developed diabetes during 1 year follow-up. Diabetes incidence rate was relatively comparable who used varenicline and bupropion (23.50 versus 25.80 per 1, 000 person-years). Obese smokers who were prescribed bupropion had a statistically significant higher risk of developing diabetes during 1 year following cessation treatment than those who were prescribed varenicline. ([HR]: 1.58, 95% CI: 1.09–2.27) in the multivariate model. Conclusions/Importance: Obese smokers who were prescribed bupropion might have a higher risk of developing diabetes during 1 year follow up compared to those who were prescribed varenicline. The clinical significance of the finding that bupropion had a higher risk of developing diabetes may need further investigation.